Estudo genético-clínico da displasia coxofemoral em cães shih tzu através de polimorfismos de nucleotídeos simples (SNPs) - Sônego, Dábila Araújo (2018)
The objective of the study was to verify the incidence of coxofemoral dysplasia (DCF) in Shih Tzu dogs by radiographic examination and genetic research using three simple nucleotide polymorphisms (SNPs) already associated with disease in other races. In all 36 dogs of the Shih Tzu breed were included and submitted to ventrodorsal pelvic radiography under anesthesia. The images were analyzed by three evaluators, independently, for classification according to the Organization for For Animals (OFA) and International Cynological Federation (FCI) regarding the presence or absence of DCF and its degree. From all animals, whole blood EDTA samples were collected, from which DNA extraction, polymerase chain reaction (PCR) amplification and sequencing of the regions corresponding to SNPs BICF2G630227898, BICF2G630339806 and BICF2S2459425 were performed. Radiographic changes, articular incongruity, flattening of the femoral head and acetabular deviation were the most frequent alterations, in 97%, 97% and 91% of the evaluated population, respectively. According to the severity of these radiographic findings, 61% of the dogs were classified according to OFA with DCF, while 28% according to the FCI scale. Referring to the genetic analysis, all sequenced BICF2G630227898 SNPs, 86% SNP BICF2G630339806 and 27% SNP BICF2S2459425. A second SNP was identified in the sequenced region near BICF2S2459425 in 62% of the sequenced. The morphological difference of the involvement in relation to large races to the radiographic examination, referred to the occurrence of a different disease in Shih Tzu, but the presence of the SNPs indicates to be the same pathogenesis influenced by different biomechanical factors, to conclusion, the occurrence must be evaluated in a broader population.